ACCURATION OF INDONESIAN RICE SUPPLY AND DEMAND FORECASTING FOR FOOD AVAILABILITY - Henik Prayuginingsih (UPT Penerbitan Universitas Jember, 2017)
Accuration of forecasting is very usefull as a base for policy making in the future. Thisstudy aimed to test accuration of Indonesian rice supply and demand forecasting in 2015which was made in 2006. Study was done on national scale used secondary data between 1970-2004 which was obtain from legitimate institution publication. Forecasting was donethrough these steps : (a) model equation arranging, (b) model identifying, (c) modelestimating and parameter testing by two stage least square methode using SAS programanalysis software, (d) model validation test, and (e) exogenous variable forecasting usingexponential smoothing methode. Forecasting result was compared with official data in 2015published by Center for Agriculture Data and Information System, Ministry of Agriculture Republik of Indonesia (2016). Accuration was based on % deviation between official sourceand forecasting result, the more deviation the more non accurate. The results were: (a) Therewas a big deviation (109.16%) between official source and forecasting calculation onIndonesian food avaiability in 2015. Based on official source, Indonesian rice supply was44,710,528 tonnes, demand was 32,388,271 tonnes and availability was surplus 12,322,257tonnes. The main cause of surplus was over estimate of harvested area. On the contraryaccording to forecasting, supply was 40,894,521 tonnes, demand 42,023,699 tonnes, andIndonesian food availability was deficit 1,129,178 tonnes. The main cause of deficit was usingof previous estimate of consumption/capita/year which was larger than official source sodemand became larger too. None of these calculation was matching with actual condition;(b) Simulation using forecasting data which was calculated by official source way found outthat food availability which more close to real condition, that domestic production plus861,630 tonnes amount of imported rice could fulfil demand and without calculatingnational stock Indonesian food availability still surplus 1,164,574 tonnes in 2015.